Implementing crossword puzzles using crosswordlabs.com in the campus program teaching at an elementary school - Rohmah, Siti Nur; Aeni, Candra; Panggabean , Christina Innocenti Tumiar (Digital Theory, Culture & Society, 2024)
Islamic religious education learning is an important part of the educational curriculum that aims to form a good understanding, values and attitudes towards Islamic teachings. In order to increase student participation and change the learning atmosphere, it is necessary to use engaging learning media. One of the most widely used and practical media is crossword puzzles. This study aims to describe or explain the students’ responses towards the use of crossword media in Islamic religious education learning at SDN Kesamben II Plumpang. The research method is qualitative descriptive research. The data were obtained through direct observation, interviews, and analysis of documents related to the use of crossword media in Islamic religious education learning. The research participants consisted of thirty students of fourth, fifth, and sixth grade learning Islamic religious education at SDN Kesamben II Plumpang. The result shows that the use of crossword puzzle media in Islamic religious education learning has several advantages and has a positive impact on students’ learning activities. It can be concluded that the use of crossword media can be an alternative that attracts students to learn Islamic religious education.